Mining Contratação License in the New Regulatory Framework of Brazilian Mining: Some Notes on the Institutes of Research Authorization and Mining Concession (Revista Brasileira Multidisciplinar, 2013)
Given the importance of mining nowadays, Government seeks ways to stimulate its growth, focusing on potentializing research and the advancement of mineral processing, the basic items for speeding up this activity in a profitable way. In this sense, the discussions on the crystallization of a new regulatory framework for the Brazilian mining have been deepened and, despite gathering a significant number of proposals, it does not have a closed text, and, currently, it is far from obtaining an approval or a final word (despite the urgency). However, the analysis of the proposals that have been presented reveals that there is an intention to institute new rules for the modernization of Brazilian mining, and this paper has the purpose of suggesting ways to reconcile conflicts permeated by various dissonant interests that surround the Brazilian mining at this time. It should be emphasized that, given the lack of official disclosure of the amendments proposed, the approach will continue limited to what has been released by MME (Ministry of Mines and Energy) and by the studies that have already been presented by experts in the field (connected to government and/or private businesses). It is restricted to discuss changes to be implemented with the new regulatory framework, highlighting points to be observed, and, among the topics that require mandatory update, we can emphasize the changes in the procedures of exploration permits and mining.
Keywords: Mining; New regulatory framework; Economic exploitation; Mineral Rights.